Bio-inspired acetal induced polyene cyclization : the development and applications - Li, Bin (2013)
The development of a bio-inspired acetal induced intermolecular polyene cyclization is described. This process has been successfully applied to construct terpenoids skeletons and the core structure of Cortistatin A between chiral acetals and silyl enol ethers. On the other hand, a direct method to construct 2-functionalized terpenoids was developed by using isobutene as the other component. In addition, this strategy was further extended to construct 7-6-6 fused rings. Interestingly, TiCl4 and SnCl4 gave different diastereomers.